"Problematiken som slår klorna i en". En kvalitativ studie om socialarbetares perspektiv på arbetet med barn till missbrukande föräldrar. - Börkell,Sandra; Brandt,Amanda (2015)
Authors: Sandra Börkell & Amanda Brandt Title: “The problem that strikes its claws into you” – A qualitative study of Social Workers’ point of view on their work with children of addicted parents. [Translated title] Supervisor: Eva Palmblad Assessor: Weddig Runquist The aim of this essay was to study, from a social worker’s point of view, their thoughts and experiences in helping children who suffer in families where drug abuse is an evident issue. With the assistance of qualitative semi-structured interviews as a choice of method we have been able to interview six social workers. The six of them were either currently working as Child protection social workers or they have in their earlier professional career. We have had our focus on four themes which has also been the foundation of the interviews: professional role, discretion, dilemma with respect to children’s perspective in order to receive the result we were looking for. The essay also contains theoretical concepts according to the professional role and discretion of the social worker. The main result shows that the social workers perceive ambivalence in their decision-making, especially towards families where the parents won’t acknowledge their addiction or when they’re refusing interventions. Another general issue has to do with the lack of time in the process of helping children who live in drug abused homes. The result also shows that the ability to create trust and an alliance with the parents and children are significant in order to make a positive change in their lives. However, the law, the organizational set of regulations, the discretion of the social worker, the parents’ consent to interventions and sometimes the parents’ denial of their addiction are what makes social work with these children complex and challenging. Keywords: drug abuse, professional role, street-level bureaucrat, discretion, child perspective Nyckelord: drogmissbruk, professionell roll, gräsrotsbyråkrat, handlingsutrymme, barnperspektiv
Keywords: professionell roll; child perspective; discretion; street-level bureaucrat; drug abuse; professional role; drogmissbruk; gräsrotsbyråkrat; handlingsutrymme; barnperspektiv